2019
DOI: 10.2174/1874306401913010019
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Ocular Complications in Obstructive Sleep Apnea Patients: A Cross-sectional Case-control Study

Abstract: Purpose:This study sought to identify the magnitude and the possible risk factors of ocular complications in patients with Obstructive Sleep Apnea (OSA).Methods:A hospital-based cross-sectional study with a nested case-control design was conducted. Qualifying study subjects were patients who had been diagnosed with moderate to severe OSA (AHI index of ≥ 5, n=80), and control subjects (n=20) who had an AHI index of ≤ 5 (“normal”). Study participants were recruited from Mansoura University Hospital’s Sleep Disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 50 publications
(61 reference statements)
0
20
1
1
Order By: Relevance
“…Unlike previous findings that reported a significant association of cataracts and DM or OSA alone [15], we failed to observe any significant relationship between them in multivariate analysis. Possible explanations for this discrepancy follow.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Unlike previous findings that reported a significant association of cataracts and DM or OSA alone [15], we failed to observe any significant relationship between them in multivariate analysis. Possible explanations for this discrepancy follow.…”
Section: Discussioncontrasting
confidence: 99%
“…Its risk factors include increasing age, female sex, genetic factors (e.g., chromosome 3 in KCNAB1 and chromosome 21 in CRYAA), lifestyle factors (e.g., ultraviolet-B exposure, cigarette smoking, and alcohol consumption), consumption of carbohydrates with a high glycemic index, and systemic and medical problems (e.g., type 2 DM, high systemic blood pressure, and metabolic syndrome) [14]. Although few studies have reported the association of OSA with cataracts, a recent cross-sectional study reported the magnitude and risk factors of ocular complications in OSA patients associated with a greater risk of senile cataracts [15]. However, to our knowledge, no study has investigated the association between OSA and cataracts in a large population-based prospective cohort study.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, only patients aged over 50 years had been included in that study. Additionally, Morsy et al (2019) found in their study with 80 participants that OSA is associated with a higher risk of vision-threatening and non-threatening ocular disorders. The lowest oxygen desaturation index in OSA patients was a significant predictor of vision-threatening disorders [9].…”
Section: Discussionmentioning
confidence: 98%
“…A link between OSA and glaucoma has been proposed [5][6][7][8][9][10]. Specifically, it is assumed that OSA might partly cause or worsen glaucoma [5].…”
mentioning
confidence: 99%
“…Besides ocular surface damage, further ocular manifestations of OSA include floppy eyelid syndrome (FES), glaucoma, nonarteritic anterior ischemic optic neuropathy and central serous retinopathy [11,12]. Based on these observations in the published literature, an extensive ophthalmic examination should be implemented in patients with confirmed OSA [13]. Accompanying ocular problems are often not seen in connection with continuous positive airway pressure therapy, increasing communication between ophthalmologists and sleep medicine specialists recognizing DED in patients with OSA.…”
mentioning
confidence: 99%